One‐hour oral glucose tolerance test plasma glucose at gestational diabetes diagnosis is a common predictor of the need for insulin therapy in pregnancy and postpartum impaired glucose tolerance. Issue 6 (29th April 2018) - Nishikawa, Takeshi; Ono, Keiko; Hashimoto, Shoko; Kinoshita, Hiroyuki; Watanabe, Takuro; Araki, Hirotaka; Otsu, Kae; Sakamoto, Wakana; Harada, Masahiro; Toyonaga, Tetsushi; Kawakami, Shoichi; Fukuda, Jyunichiro; et al.
Abstract: Aims/Introduction: Gestational diabetes mellitus (GDM) is a risk for adverse perinatal outcomes, and patients with a history of GDM have an increased risk of impaired glucose tolerance (IGT). Here, we carried out two non‐interventional and retrospective studies of GDM patients in Japan. Materials and Methods: In the first study, we enrolled 529 GDM patients and assessed predictors of the need for insulin therapy. In the second study, we enrolled 185 patients from the first study, and assessed predictors of postpartum IGT. Results: In the first study, gestational weeks at GDM diagnosis and history of pregnancy were significantly lower, and pregestational body mass index, family history of diabetes mellitus, 1‐ and 2‐h glucose levels in a 75‐g oral glucose tolerance test (OGTT), the number of abnormal values in a 75‐g OGTT, and glycated hemoglobin were significantly higher in participants receiving insulin therapy. In the second study, 1‐ and 2‐h glucose levels in a 75‐g OGTT, the number of abnormal values in a 75‐g OGTT, glycated hemoglobin, and ketone bodies in a urine test were significantly higher in participants with OGT. Logistic regression analysis showed that gestational weeks at GDM diagnosis, 1‐h glucose levels in a 75‐g OGTT and glycated hemoglobin were significant predictors of the need for insulin therapy, and 1‐h glucose levels in a 75‐g OGTT at diagnosis and ketone bodies in a urine test were significant predictors for postpartum IGT. Conclusions: Antepartum 1‐h glucose levels in a 75‐g OGTT was a predictor of the need for insulin therapy in pregnancy and postpartum IGT. Abstract : We performed two non‐interventional and retrospective studies of GDM patients in Japan to assess predictors of the need for insulin therapy in pregnancy, and predictors of postpartum impaired glucose tolerance. Gestational weeks at GDM diagnosis, plasma glucose levels in a 75 g OGTT at 1 hour, and HbA1c were significant predictors of the need for insulin therapy, and 1‐hour glucose levels in a 75 g OGTT at diagnosis and ketone bodies in a urine test were significant predictors for impaired glucose tolerance during the 6‐to‐12‐weeks postpartum period. In particular, antepartum 1‐hour glucose levels in a 75 g OGTT was a predictor of both the need for insulin therapy in pregnancy and postpartum impaired glucose tolerance.